APPROVAL OF PARAMETERS OF IRRADIATION REGIME OF SEED POTATO WITH UBN USING THE METHOD OF MATHEMATICAL PLANNING OF EXPERIMENTS - Sanbetova A. T. (International Journal of Innovations in Engineering Research and Technology, 2023)
Optimal values of the parameters studied in fundamental and single-factor experimental studies on UBN exposure to DNA at the cellular level and UBN treatment of potato parenchyma were determined using the method of mathematical planning of multifactorial experiments. In order to ensure the food security of the population of the earth by increasing the quality indicators of the seeds of agricultural crops, including potato seeds, ecologically clean, disease and pest resistant seeds and potatoes for the consumer in the world, energy and resource efficient and high productivity agrotechnologies and their implementation creation and introduction of technical means to production takes one of the leading positions.